Be My Wife - LeGuen, Eric (Max Linder: Les longs métrages américains, 2014)
Although he had just recently returned to the United States and formed his own studio, comedian Max Linder's career was nearing an end. Here, he plays an eager suitor whose girlfriend (Alta Allen) has a stern and disapproving maiden aunt (Carolyn Rankin). The whole picture centers around Max's many attempts to win over the aunt, and the highlight is a scene in which he battles an imaginary intruder - actually himself - while his girl and aunt are shaking with fright in another room (Charley Chase later did something similar in his 1926 short, "Mighty Like a Moose"). After a number of other slapstick antics, a couple involving mice scurrying around in people's clothes, Max finally wins the girl. This feature was funny enough, although some of the jokes were on the musty side. But Linder had been so far surpassed by Charles Chaplin - who he strongly influenced - that this, and his other two 1921 pictures, paled in comparison. Soon after he completed these films, Linder would return to France where, in 1925, he would commit suicide. [www.allmovie.com]